Charge and spin transport in monolayer and few-layer graphene nanostructures - Liu, Yanping (2013)
In this thesis, charge and spin transport experiments on monolayer and few-layer graphene are presented. The research revolves around fabrication and understanding the fundamental properties of graphene. Magneto transport measurements suggest that a gap is generated due to the Landau level splitting. In further experiments, graphene nanomesh was fabricated by etching monolayer sheets into small mesh (diameter 40~60 nm) and the resistance dependence on the magnetic field and temperature are studied. The first report of a weak localization (WL) effect in monolayer graphene nanomesh is presented. The observed WL is evidence of lattice defects in graphene nanomesh acting as resonant scatterers that contribute to the intervalley scattering. Lastly, graphene-based spin valve devices with a ferromagnetic-MgO-graphene (F/I/G) structure in lateral geometry were fabricated for the investigation of the spin transport properties. The first observation of a long spin diffusion length of 2.0 μm in trilayer graphene is presented in this thesis. The observed results indicate that trilayer graphene is a promising candidate for application in spintronic devices.